The cumulative effect of repetitive concussion in sports - Rabadi, M. H.; Jordan, B. D. (Clinical Journal of Sport Medicine, 2001)
The increased popularity of contact sports worldwide exposes a large number of participants to both acute and chronic traumatic brain injury. Chronic traumatic brain injury (CTBI) represents the cumulative, long-term neurological consequences of repetitive concussive and subconcussive blows to the brain. Although this condition has been described primarily in boxing, it may be anticipated in other contact sports such as soccer, football, ice hockey, and the martial arts. Since treatment options in CTBI are relatively limited, the prevention of CTBI is of paramount importance. Minimizing the frequency and severity of acute brain injury in sport will be instrumental in accomplishing this goal. The prevention of CTBI will need to be sport specific and will undoubtedly rely on limiting the exposure of high-risk athletes, utilizing of protective equipment, enforcing strict rule adherence, training and supervising athletes, and increasing medical surveillance.